1992
DOI: 10.1001/archsurg.1992.01420120030005
|View full text |Cite
|
Sign up to set email alerts
|

Potency, Cure, and Local Control in the Operative Treatment of Rectal Cancer

Abstract: Impotence due to parasympathetic nerve injury is one of the most feared consequences of operations for treatment of rectal cancer. Sharp dissection along the parietal pelvic fascia where the parasympathetic nerves are located significantly reduces the incidence of pelvic failure. Autonomic nerve-preserving pelvic sidewall dissections, which combined the benefits of en bloc parietal pelvic dissection with nerve preservation, were performed in 42 men who were undergoing sphincter-preserving operations for treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
91
0
7

Year Published

1995
1995
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 247 publications
(103 citation statements)
references
References 29 publications
3
91
0
7
Order By: Relevance
“…Correctly performed, TME proceeds along defined avascular planes and avoids perforation of the mesorectum which can lead to tumour spillage and contamination and increase the risk of disease dissemination. The application of this technique significantly improved the possibility of achieving a negative CRM and thus reduced the incidence of local recurrence (3,25,26). In an analysis of observational studies from a number of countries, prospective outcomes of 691 patients with Stage II or III rectal cancer who underwent TME surgery at three specialized oncology centres (US, UK, Japan) in 1978-1994 were compared with 720 similar stage patients who underwent conventional surgery at multiple Norwegian and Dutch community hospitals in 1986-1993 (27).…”
Section: The Role Of Surgical Techniquementioning
confidence: 99%
“…Correctly performed, TME proceeds along defined avascular planes and avoids perforation of the mesorectum which can lead to tumour spillage and contamination and increase the risk of disease dissemination. The application of this technique significantly improved the possibility of achieving a negative CRM and thus reduced the incidence of local recurrence (3,25,26). In an analysis of observational studies from a number of countries, prospective outcomes of 691 patients with Stage II or III rectal cancer who underwent TME surgery at three specialized oncology centres (US, UK, Japan) in 1978-1994 were compared with 720 similar stage patients who underwent conventional surgery at multiple Norwegian and Dutch community hospitals in 1986-1993 (27).…”
Section: The Role Of Surgical Techniquementioning
confidence: 99%
“…Tumor recurrence due to the implantation sometimes occurs in the operating field, or in different places depending on the performed surgical procedure (19). There are many reports describing the implantation of tumor cells on the trocar sites during laparoscopic procedures (20). Vukasin et al have reported this ratio as 1.1% (10).…”
Section: Discussionmentioning
confidence: 99%
“…Before the adoption of total mesenteric excision (TME) [19,20], surgery alone for transmural or node positive rectal cancer was associated with local recurrence rates of up to 50% [21,22]. This provided the rationale for exploration of management plans to improve outcomes following resection.…”
Section: Tumour Markersmentioning
confidence: 99%